2x+6=2(x-3)3

Simple and best practice solution for 2x+6=2(x-3)3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+6=2(x-3)3 equation:



2x+6=2(x-3)3
We move all terms to the left:
2x+6-(2(x-3)3)=0
We calculate terms in parentheses: -(2(x-3)3), so:
2(x-3)3
We multiply parentheses
6x-18
Back to the equation:
-(6x-18)
We get rid of parentheses
2x-6x+18+6=0
We add all the numbers together, and all the variables
-4x+24=0
We move all terms containing x to the left, all other terms to the right
-4x=-24
x=-24/-4
x=+6

See similar equations:

| 4x+7-9x=25-5x | | b+36=7b | | 2(x-4)5=-x+4 | | n9=6 | | f+9=35 | | 4x-3-14=-1 | | c+5=63 | | 3(x+4)+4x=-37 | | f6=6 | | x+36=38 | | 6x+2x+30=110 | | d−21=69 | | -34=-2y+4(y-5) | | –19f=11−18f | | b/23-5=13 | | j+14=32 | | c+42=50 | | 4q^2=64 | | 6+17b=14+16b | | 3z-32=z | | 18=10-2w | | 5.12p+7.1=-2.2 | | c+64=225 | | 4q^2-64=0 | | 7h=–19+6h | | 3u-39=u+1 | | 11w=-16=7w | | 3x-14x=-55 | | 8x=20=2x+34 | | 3x+12=2x-18 | | 1.2l+7=13.24 | | 11t-28=7t |

Equations solver categories